Samos, Griechenland. Wasser und Kult im Heraion von Samos. Die Arbeiten der Jahre 2016 bis 2017 - Fuchs, Johanna (e-Forschungsberichte des DAI, 2017)
In the Sanctuary of Hera on the Greek island of Samos a wide range of hydrotechnical elements has been excavated. Well over one hundred fountains, basins, cisterns, channels and pipelines have been recorded. Since the end of 2016, a joint research project of the German Archaeological Institute and the Lübeck University of Applied Sciences aims to analyse these structures in terms of geohydrology, water management and hydraulic engineering and to examine their role in the cult activities. In the first of three years run-time the interdisciplinary team focused on collecting data, both in archives and on site. During a field-campaign in summer 2017 soil and sediment as well samples of water and calcium carbonate deposits (sinter) were taken.